Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jtho.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction modelling using routine clinical parameters to stratify survival in Malignant Pleural Mesothelioma patients undergoing cytoreductive surgery

Abstract: Introduction: Malignant pleural mesothelioma (MPM) is an uncommon cancer with a poor prognosis and heterogeneous survival. Surgery for MPM is offered in some specialist centers to highly selected patients. A previously described classification and regression tree (CART) model stratified survival in unselected MPM patients using routinely collected clinical data. This study aimed to examine the performance of this CART model on a highly selected surgical population. Methods: Data were collected from subjects un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In a classification and regression tree analysis, Brims et al found the best survival for patients with no weight loss, a high hemoglobin level and a high serum albumin level [176]. Harris et al validated these findings for surgical patients undergoing cytoreductive surgery [175].…”
Section: Albumin-a Negative Acute Phase Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a classification and regression tree analysis, Brims et al found the best survival for patients with no weight loss, a high hemoglobin level and a high serum albumin level [176]. Harris et al validated these findings for surgical patients undergoing cytoreductive surgery [175].…”
Section: Albumin-a Negative Acute Phase Proteinmentioning
confidence: 99%
“…In addition, it was described to indicate short survival in different malignancies [168]. For MPM, hypoalbuminemia has been associated with poor survival for patients receiving different treatment modalities [102,103,114], but also selectively for chemotherapy patients [174] and surgical patients [175].…”
Section: Albumin-a Negative Acute Phase Proteinmentioning
confidence: 99%
“…This study demonstrated that the BRIMS score might be useful in prognosis risk stratification of patients, which was similar to a previous study. 19 The strongest predictive variable in the BRIMS score was weight loss, which is controversial. 20,21 In this study, the median time from the discovery of pleural effusion to the diagnosis of pleural mesothelioma was 60 days, and 81.2% of the patients were diagnosed using thoracoscopy, which reduced the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of weight loss with ECOG PS of 2 or more, or weight loss, ECOG PS 0-1 with sarcomatoid histology, conferred the worst median (interquartile range: IQR) survival of 7.4 (3.3 to 11.1) months, whereas the combination of no weight loss, normal haemoglobin and normal serum albumin was associated with the best survival with a median (IQR) 34.0 (22.9-47.0) months [76]. The model has been validated in different populations of MPM patients and may help stratify risk groups to inform different treatment options and discussions with patients and their families [115,116].…”
Section: Prognosismentioning
confidence: 97%